KONSTRUKSI BANGUNAN SEBAGAI IDE PENCIPTAAN SENI RUPA DENGAN EKSPLORASI TEKNIK SENI GRAFIS - Nugraha Heru Cahyono (CILPA, 2021)
Creation of artwork is a true expression of feelings and mental turmoil, which is a collection of ideas that come from the environment, the physical experience, inner experience and amazing events experienced by the artist. Construction is very close to the author environment, from the frequent notice consciously or unconsciously derive pleasure when looking at the construction forms, the impression of the experience into an embryo that would be the idea of the creation of art works which is based on form of construction. Construction of the building has a strong character, sturdy, have an artistic texture on a surface, interrelated nature intertwined, construction also has a tendency to repetitive, and often there is rust on a surface that is the main attraction of outstanding artistic. The forms of construction, and characteristics of the meaning contained in construction has more potential and opportunity when realized in various printmaking techniques, because with printmaking techniques we will obtain artistic surprises that can’t be predicted, and the printmaking techniques will be able to easily duplicate these forms of construction that will add an artistic work. With the exploration of printmaking techniques, will be a personal language of expression, because the printmaking has a wide variety of technical and characters are unique and different. Construction of the building material and the characteristics have artistic power that could be disclosed to a variety of visual forms that can lead to a whole new image and meaning are processed according to the character and personal self interest, that’s as an expression of pure expression to reach artistic satisfaction and also as form of language to respond to social reality.